Quantification of adhesion of mesenchymal stem cells spread on decellularized vein scaffold - Rodrigues, Lenize da Silva [UNESP]; Bovolato, Ana Lívia de Carvalho [UNESP]; Silva, Bárbara Esteves [UNESP]; Chizzolini, Leticia Victória [UNESP]; da Cruz, Bianca Latance [UNESP]; Moraes, Marcelo Padovani de Toledo [UNESP]; Lourenção, Pedro Luiz Toledo de Arruda [UNESP]; Bertanha, Matheus [UNESP] (FapUNIFESP (SciELO), 2021)
Purpose: To evaluate methods that improve adipose-derived stem cells (ASCs) population in decellularized biological venous scaffold for tissue engineering in blood vessels, a model in rabbits. Methods: The ASC was expanded until the third passage. Inferior vena cava (IVC) was submitted to the decellularization process using 1% sodium dodecyl sulfate (SDS) or 2% sodium deoxycholate (SD) to compose 12 study groups (G): pure SD or SDS, exposed or not to 1% TritonX-100 (TX-100) and exposed or not to poly-l’lysine and laminin (PL). Scaffolds were covered with 1 × 105 or 1 × 106 ASCs diluted in 10 μL Puramatrix™. The histological analysis was done by cell counting in hematoxylin and eosin (HE) and nuclei count in immunofluorescence (IF) with 4’,6-Diamidine-2’-phenylindole dihydrochloride (DAPI). Results: The study of groups in HE and IF showed similar results. For both analyses, IVC-SD-1 × 106 ASC and IVC-SD-PL-1 × 106 ASC provided the best results. The IF technique showed better sensitivity than HE, with a weak agreement between them. Conclusion: Decellularizing agent and the number of ASC influence scaffolds cellularization response and the best protocols as those ones using SD with or without the addition of PL.
Keywords: Blood vessels; Endothelium; Mesenchymal stem cells; Peripheral arterial disease